Metabolic characteristics and therapeutic potential of brown and ?beige? adipose tissues - Ekaterina Olegovna Koksharova (Endocrinology Research Centre, 2014)
According to the International Diabetes Federation, 10.9 million people have diabetes mellitus (DM) in Russia; however, only up to 4 million are registered. In addition, 11.9 million people have impaired glucose tolerance and impaired fasting glucose levels [1]. One of the significant risk factors for type 2 DM (T2DM) is obesity, which increases insulin resistance (IR). IR is the major pathogenetic link to T2DM. According to current concepts, there are three types of adipose tissue: white adipose tissue (WAT), brown adipose tissue (BAT) and ?beige?, of which the last two types have a thermogenic function. Some research results have revealed the main stages in the development of adipocytes; however, there is no general consensus regarding the development of ?beige? adipocytes. Furthermore, the biology of BAT and ?beige? adipose tissue is currently being intensively investigated, and some key transcription factors, signalling pathways and hormones that promote the development and activation of these tissues have been identified. The most discussed hormones are irisin and fibroblast growth factor 21, which have established positive effects on BAT and ?beige? adipose tissue with regard to carbohydrate, lipid and energy metabolism. The primary imaging techniques used to investigate BAT are PET-CT with 18F-fluorodeoxyglucose and magnetic resonance spectroscopy. With respect to the current obesity epidemic and associated diseases, including T2DM, there is a growing interest in investigating adipogenesis and the possibility of altering this process. BAT and ?beige? adipose tissue may be targets for developing drugs directed against obesity and T2DM.